State civil disobedience: morally justified violations of international law considered as civil disobedience - Gerald Neubauer (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2009)
International legalization promises to civilize world politics with global legal norms that bind states' behavior effectively. However, international legal norm can also institutionalize unjust forms of cooperation and the dominance of powerful states. In order to challenge unjust global rules the concept of civil disobedience has to be extended to international law violations by sovereign states. In the national realm civil disobedience has contributed extensively to the establishment of human rights. In order to use the concept for international politics, this paper develops criteria for state civil disobedience which are then applied to the Argentine foreign debt repudiation and Bolivia's violations of international investment law. Furthermore two hypotheses concerning causes and consequences of state civil disobedience are formulated – – Internationale Verrechtlichung verspricht eine Zivilisierung der Weltpolitik durch eine effektive Bindung der Staaten an globale Rechtsnormen. Gleichwohl können internationale Rechtsnormen auch die Dominanz der mächtigeren Staaten institutionalisieren und ungerechte Kooperationsformen festschreiben. Um ungerechte globale Rechtsnormen zu verändern ist es notwendig den Ansatz des zivilen Ungehorsams auf staatliche Rechtsbrüche zu übertragen. Im nationalen Rahmen hat der zivile Ungehorsam durch begrenzte Rechtsbrüche einen erheblichen Beitrag für die Erkämpfung der Menschenrechte geleistet. Um dieses Potential für die internationale Politik nutzbar zu machen, werden Kriterien für staatlichen zivilen Ungehorsam entwickelt und auf die argentinische Schuldenverweigerung und Boliviens Verletzungen internationalen Investitionsrechts angewendet. Zudem entwickelt das Papier zwei Hypothesen zu den Ursachen und den Wirkungen von staatlichem zivilem Ungehorsam
Keywords: 340